Grammatical Barriers in Writing A German Essay: A Case Study of Secondary High School Students - Ester Sri Melanda; Juliyanti Margaretta; Riza Alamsyah (Universitas Negeri Malang, 2021)
Abstract : This research was conducted to identify the grammatical barriers most often carried out by high school students. This type of research is a case study research to reveal the grammatical errors obtained instead of writing essays. These researchers uses a qualitative descriptive study. The data in this study are the results of German sentences written by 10 students in an essay, which then identified and classified the error Grammatically reviewed by Morphology and Syntax. The types of grammar errors analyzed specifically: capitalization, conjugation, verbposition , personalpronomen and article.